Insights into the effects produced by doping of medium-sized boron clusters with ruthenium. Issue 48 (29th November 2018) - Chen, Bole; Sun, Weiguo; Kuang, Xiaoyu; Lu, Cheng; Xia, Xinxin; Shi, Hongxiao; Gutsev, Gennady L.
Abstract : The global-minimum structures of RuB n 0/− ( n = 9–20) clusters have been determined by the CALYPSO method combined with DFT calculations. Abstract : Modification of properties of boron nanoparticles by doping with transition metals presents a challenging problem because the number of isomers of both doped and un-doped nanoparticles rapidly increases with the nanoparticle size. Here, we perform a study of neutral and anionic Ru-doped boron clusters RuB n ( n = 9–20) using the unbiased CALYPSO structural search method in combination with density functional theory calculations. Our results show that the neutral RuB9 cluster possesses a perfect planar wheel-like geometrical structure, whereas the RuB n clusters prefer structures of the half-sandwich type in the range of 10 ≤ n ≤ 14, drum-like type in the range of 15 ≤ n ≤ 18 and cage-like structures for larger n values. The geometrical structures of the lowest total energy states of the RuB n − anions are similar to those of the corresponding neutrals, except for RuB10 −, RuB11 −, RuB14 −, RuB15 − and RuB20 − . The neutral RuB12 and RuB14 clusters are found to exhibit enhanced stability with respect to the rest of the RuB n clusters due to the delocalized bonding between the Ru atom and the boron host.